Education and family background: Mechanisms and policies - Anders Björklund; Kjell G. Salvanes (Institute for the Study of Labor (IZA), 2010)
In every society for which we have data, people's educational achievement is positively correlated with their parents' education or with other indicators of their parents' socioeconomic status. This topic is central in social science, and there is no doubt that research has intensified during recent decades, not least thanks to better data having become accessible to researchers. The purpose of this chapter is to summarize and evaluate recent empirical research on education and family background. Broadly speaking, we focus on two related but distinct motivations for this topic. The first is equality of opportunity. Here, major the research issues are: How important a determinant of educational attainment is family background, and is family background - in the broad sense that incorporates factors not chosen by the individual - a major, or only a minor, determinant of educational attainment? What are the mechanisms that make family background important? Have specific policy reforms been successful in reducing the impact of family background on educational achievement? The second common starting point for recent research has been the child development perspective. Here, the focus is on how human-capital accumulation is affected by early childhood resources. Studies with this focus address the questions: what types of parental resources or inputs are important for children's development, why are they important and when are they important? In addition, this literature focuses on exploring which types of economic policy, and what timing of the policy in relation to children's social and cognitive development, are conducive to children's performance and adult outcomes. The policy interest in this research is whether policies that change parents' resources and restrictions have causal effects on their children.
Keywords: I21; J13; J24; 330; Intergenerational mobility; sibling correlations; education; education reform; Bildungsabschluss; Generationenbeziehungen; Familiensoziologie; Intergenerational Mobility; Theorie